Extramural French among university students in Sweden - Arvidsson, Klara; Rocher Hahlin, Céline (Moderna Språk, 2022)
The purpose of this study is to better understand conditions for foreign language (FL) learning in Sweden. Research suggests that foreign language learners benefit from informal target language (TL) exposure and use outside the classroom (e.g., Peters, 2018; Sundqvist, 2009). While studies conducted in a Swedish context show that there are rich opportunities to come in contact with the English language outside the classroom, little is known about the learners’ extramural exposure to and use of other FLs. In analogy with the term ‘Extramural English’ (Sundqvist, 2009), this study explores ‘Extramural French’. The study includes 59 university students enrolled in a French language course. Using the survey method, we investigated the participants’ engagement in Extramural French (frequency and type), and the relationship between language learning motivation, self-assessed proficiency, and frequency of Extramural French. The results showed that about half of the sample engaged in Extramural French on a relatively frequent basis. The most frequent extramural activities included listening to music, watching TV and films, and browsing online. About a third of the sample had regular access to social interaction in French. In addition, language learning motivation increased the likelihood to spend time on Extramural French activities. Overall, the study provides insights into the conditions for FL learning in a Swedish context.